Yearbook of the United Nations 2011 - United Nations (United Nations, 2015)
With its comprehensive coverage of political and security matters, human rights issues, economic and social questions, legal issues, and institutional, administrative and budgetary matters, the Yearbook of the United Nations stands as the most authoritative reference work on the activities and concerns of the Organization. Fully indexed, the Yearbook includes the texts of all major General Assembly, Security Council and Economic and Social Council resolutions and decisions, putting all of these in a narrative context of United Nations consideration, decision and action.